Pengalaman Perawat Berkolaborasi dengan Dokter di Ruang ICU - Brita Rahaminta; Madya Sulisno (Jurnal Keperawatan Diponegoro, 2012)
Collaboration in the health care involve nurses and physicians as the crucial determinant of the quality of care process. Moreover, as time goes by, the need of collaboration between nurses and physicians has been growing up professionally. Critical nursing area, esspecially Intensive Care Units (ICU) is one of area has proven to help understanding collaboration between nurses and pyhsicians. The purpose of the research was to explore nurses’ experience in doing the elements to achieve effective collaboration with physicians in Intensive Care Units (ICU) Ambarawa Hospital. This was a qualitative research with phenomenological approach. The data were collected using in depth interview method to 3 samples chosen by purposive sampling method using considerations those sample whose experience as the nurse leader in ICU, whose experience working in ICU since it was built and whose experience working in ICU less than a year. This research showed that the implementation of elements to achieve effective collaboration between nurses and physicians included of cooperation, assertiveness, responsibility, communication, autonomy, coordination, mutual respect and determine the common purpose.  The research concluded that effective collaboration was motivated by desirability to achieve common purpose of collaboration for patients’ satisfaction, showed by the right implementation of the cooperation, assertiveness, responsibility, communication, autonomy, coordination with mutual respect as the avalist of the success